DETERMINATION OF INCREASING SMES'S INTENTION TO USE SHARIA BANKING SERVICES: SME’S PERSPECTIVE IN MALANG - Tara Andaresta; Nihayatu Aslamatis Solekah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
The research aims to determine the influence of Shariah financial literacy, Islamic branding, and religiousness on the interests of SMEs in the use of Shariah banking services. Knowledge of Shariah finance, the application of Islamic branding, and the understanding of religiousness can influence the interest of Small Enterprise perpetrators in the Big Market of Malang City in banking services. Good financial literacy of the Shariah, an Islamic understanding of branding, and a high level of religiosity are expected to make SMEs a qualified perpetrator. This research uses a descriptive quantitative approach that uses primary and secondary data. The sample used in this study was 165 respondents of Small Enterprises offenders in the Big Market of Malang City—data obtained from questionnaires distributed offline to respondents who have qualified. The data obtained was then processed with the help of statistical software, which is SPSS version 24. The analysis used in this study is the measurement of validity and realisticity, the fulfilment of classical assumptions, the analysis of double linear regression, and the test of hypotheses. The results of this study are based on a regression test, i.e., partially, the variable of Shariah financial literacy has a significant influence on the interest in using Sharia banking services, vriable Islamic branding partially has a positive and significant influence on variable dependency, i.e., interest in using Shariah banking services, and eligiosity variables have a partially positive and significant influence on the dependent variables, i.e., interest in using Sharia banking services. The conclusion of this study is that partially the variables of financial literacy Shariah, Islamic branding, and religiousness have a positive and significant influence on the dependent variable i.e. interest in using Sharia banking services.